2015
DOI: 10.1016/j.stem.2015.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Injury Induces Direct Lineage Segregation of Functionally Distinct Airway Basal Stem/Progenitor Cell Subpopulations

Abstract: Summary Following injury, stem cells restore normal tissue architecture by producing the proper number and proportions of differentiated cells. Current models of airway epithelial regeneration propose that distinct cytokeratin 8-expressing progenitor cells, arising from p63+ basal stem cells, subsequently differentiate into secretory and ciliated cell lineages. We now show that immediately following injury, discrete subpopulations of p63+ airway basal stem/progenitor cells themselves express Notch pathway comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
171
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(181 citation statements)
references
References 36 publications
8
171
2
Order By: Relevance
“…Recently, genetic techniques have been used to kill very selectively most basal cells. In response, some Club secretory cells undergo reprogramming to become Krt5 + Trp63 + basal cells that can function as stem cells in vivo (Pardo-Saganta et al, 2015;Tata et al, 2013). Taken together, these injury/repair studies have revealed remarkable and rather unexpected flexibility in the way in which basal cells, luminal precursors and differentiated secretory cells can work together to maintain and repair the pseudostratified mucociliary epithelium of the mouse airway.…”
Section: Basal Progenitor Cellsmentioning
confidence: 99%
“…Recently, genetic techniques have been used to kill very selectively most basal cells. In response, some Club secretory cells undergo reprogramming to become Krt5 + Trp63 + basal cells that can function as stem cells in vivo (Pardo-Saganta et al, 2015;Tata et al, 2013). Taken together, these injury/repair studies have revealed remarkable and rather unexpected flexibility in the way in which basal cells, luminal precursors and differentiated secretory cells can work together to maintain and repair the pseudostratified mucociliary epithelium of the mouse airway.…”
Section: Basal Progenitor Cellsmentioning
confidence: 99%
“…[112][113][114][115][116][117] Common airway disorders include chronic obstructive pulmonary disease and asthma, for which airway organoids could provide useful models. [4] Most recent studies have shown organoids that represent early stages of lung development can be injected with respiratory syncytial virus and the lung epithelium sloughs off, which is a known consequence of this virus.…”
Section: Airway Organoidsmentioning
confidence: 99%
“…Specifically, recent studies have implicated Notch3 in promoting the differentiation of adult basal stem cells into parabasal progenitors and Notch1 and 2 in fate selection between secretory and ciliated linages (Rock et al, 2011b;Danahay et al, 2015;Mori et al, 2015;Pardo-Saganta et al, 2015). ChIP-Seq has shown Grhl2 occupancy of binding sites near NOT CH1, NOT CH3, JAG1, and JAG2 (Gao et al, 2013).…”
Section: Loss Of Grhl2 In Mouse Bcs Inhibits Epithelial Morphogenesismentioning
confidence: 99%
“…Krt5 + Trp63 + BCs of the pseudostratified mucociliary epithelium both self-renew and give rise to both Foxj1 + ciliated and secretory cells. This differentiation involves notch signaling and is thought to proceed via Trp63 + progenitors committed to either lineage pathway (yellow or blue nuclei; Mori et al, 2015;Pardo-Saganta et al, 2015;Watson et al, 2015). As progenitors and their descendants integrate into the epithelium, they acquire apical-basal polarity and apical-junctional complexes mediating barrier function.…”
Section: Ihcmentioning
confidence: 99%
See 1 more Smart Citation